2021
DOI: 10.3390/jal1010005
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Anxiety Symptoms among Adults Aged 50 Years and Over from Six Low- and Middle-Income Countries

Abstract: Currently, there are limited data on the association between multimorbidity (i.e., ≥ 2 chronic conditions) and anxiety, especially among the older population in low- and middle-income countries (LMICs). Thus, the aim of the present study was to examine the association between multimorbidity and anxiety symptoms in a large sample of adults aged ≥ 50 years from six LMICs (China, India, Ghana, Mexico, Russia, South Africa). Cross-sectional, nationally representative, community-based data from the Study on Global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These medications can elevate the risk of falls, drowsiness, and related costs, thereby contributing to increased anxiety. 43 Wongpakara et al also reported a relationship between polypharmacy and heightened anxiety in their study. 44 Furthermore, the elderly often need to invest a significant amount of time searching for health care to manage their multiple health conditions, further exacerbating their anxiety.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…These medications can elevate the risk of falls, drowsiness, and related costs, thereby contributing to increased anxiety. 43 Wongpakara et al also reported a relationship between polypharmacy and heightened anxiety in their study. 44 Furthermore, the elderly often need to invest a significant amount of time searching for health care to manage their multiple health conditions, further exacerbating their anxiety.…”
Section: Resultsmentioning
confidence: 69%
“…44 Furthermore, the elderly often need to invest a significant amount of time searching for health care to manage their multiple health conditions, further exacerbating their anxiety. 43 In this study, it was observed that elderly individuals who engaged in regular daily walks experienced lower levels of anxiety. This finding aligns with the results of studies conducted by Lu L et al, and Sirin et al 40,45 Exercise, particularly through activities like daily walking, stands out as one of the most important and accessible methods to manage anxiety among the elderly.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, mental disorders impede patients from seeking treatments, making multimorbidity management more complex and challenging. Furthermore, A cross-sectional study involving over six low and middle-income countries highlighted increased risks among the elderly with multimorbidity and anxiety ( 9 ).…”
Section: Introductionmentioning
confidence: 99%